Fe-Sem2 M2-CBCGS May18 Solution PDF
Fe-Sem2 M2-CBCGS May18 Solution PDF
Fe-Sem2 M2-CBCGS May18 Solution PDF
∞ 𝟐
Q.1.(a) Evaluate ∫𝟎 𝟓−𝟒𝒙 𝒅𝒙 [3]
∞ 𝟐
Ans: Let I = ∫𝟎 𝟓−𝟒𝒙 𝒅𝒙
𝟐
put 𝟓−𝟒𝒙 = 𝒆−𝒕
taking log on both sides,
4𝒙𝟐 𝐥𝐨𝐠 𝟓 = 𝒕
𝒕 √𝒕
𝒙𝟐 = => 𝒙=
𝟒 𝐥𝐨𝐠 𝟓 𝟐√𝒍𝒐𝒈 𝟓
diff. w.r.t x,
𝒕−𝟏/𝟐
𝒅𝒙 = 𝒅𝒕 lim⟶[ 0, ∞ ]
𝟒√𝒍𝒐𝒈 𝟓
∞ 𝒆−𝒕
∴ I = ∫𝟎 𝒕−𝟏/𝟐
𝟒√𝐥𝐨𝐠 𝟓
𝟏 ∞
∴I=
𝟒√𝐥𝐨𝐠 𝟓
∫𝟎 𝒆−𝒕 . 𝒕−𝟏/𝟐 dt
√𝝅 ∞
∴I= ………..{ ∫𝟎 𝒆−𝒕 . 𝒕−𝟏/𝟐 𝒅𝒕=√𝝅 }
𝟒√𝐥𝐨𝐠 𝟓
𝒅𝒚
(b) Solve = 𝒙. 𝒚 𝒘𝒊𝒕𝒉 help of Euler’s method ,given that y(0)=1 and find
𝒅𝒙
𝒅𝒚
Ans : = 𝒙. 𝒚 = 𝒇(𝒙, 𝒚) 𝒙𝟎 = 𝟎 , 𝒚𝟎 = 𝟏
𝒅𝒙
∴y(0.3)=1.0302
𝒅𝟒 𝒚 𝒅𝟐 𝒚
(c) Evaluate +2 + y=0 [3]
𝒅𝒙𝟒 𝒅𝒙𝟐
𝒅
Ans: put =D
𝒅𝒙
∴ 𝑫𝟒 𝒚 + 𝟐𝑫𝟐 𝒚 + 𝒚 = 𝟎
∴ 𝑫𝟒 + 𝟐𝑫𝟐 + 𝟏 = 𝟎
Put 𝑫𝟐 = 𝒕
=> 𝒕𝟐 + 𝟐𝒕 + 𝟏 = 𝟎
=> 𝒕 = −𝟏, −𝟏
Roots are : D=+i,-i,+i,-i
The complementary solution of given eqn is
𝒚𝒄 = 𝒚𝒈 = (𝑪𝟏 + 𝒙𝑪𝟐 )𝒄𝒐𝒔 𝒙 + (𝑪𝟑 +𝒙𝑪𝟒 )𝒔𝒊𝒏 𝒙
𝟏
(d) Evaluate ∫𝟎 √√𝒙 − 𝒙 𝒅𝒙 [3]
𝟏
Ans : Let I = ∫𝟎 √√𝒙 − 𝒙 𝒅𝒙
𝟏
I = ∫𝟎 √(√𝒙 − √𝒙. √𝒙 𝒅𝒙
Take √𝒙 𝒄𝒐𝒎𝒎𝒐𝒏 ,
𝟏
I =∫𝟎 𝒙𝟏/𝟒 √𝟏 − 𝒙𝟏/𝟐 dx
Put 𝒙𝟏/𝟐 = t
Squaring both sides,
2
∴ 𝒙 = 𝒕𝟐
Differentiate w.r.t x,
∴ 𝒅𝒙 = 𝟐𝒕. 𝒅𝒕
Limits after substitution : Lim ⟶[ 0,1 ]
𝟏
∴ I = ∫𝟎 𝒕𝟏/𝟐 √𝟏 − 𝒕 . 2.t dt
𝟏
= 2 ∫𝟎 𝒕𝟑/𝟐 √𝟏 − 𝒕 𝒅𝒕
𝟓 𝟑 𝟏
= 2 𝜷( , ) ……{ ∫𝟎 𝒕𝒎 . (𝟏 − 𝒕)𝒏 = 𝜷(𝒎 + 𝟏, 𝒏 + 𝟏) }
𝟐 𝟐
𝝅
∴I=
𝟖
𝑥
(e) Solve: (1+log x.y)dx + (1+ )dy = 0 [4]
𝑦
𝝏𝑴 𝟏 𝟏 𝝏𝑵 𝟏
= 𝒙= =
𝝏𝒚 𝒙𝒚 𝒚 𝝏𝒙 𝒚
𝝏𝑴 𝝏𝑵
=
𝝏𝒚 𝝏𝒙
𝟏 √𝟏+𝒙𝟐 𝒅𝒙.𝒅𝒚
(f) Evaluate I = ∫𝟎 ∫𝟎 [4]
𝟏+𝒙𝟐 +𝒚𝟐
3
𝟏 √𝟏+𝒙𝟐 𝒅𝒙.𝒅𝒚
Ans : I = ∫𝟎 ∫𝟎
𝟏+𝒙𝟐 +𝒚𝟐
I = ∫𝟎
𝟏 𝟏
[𝐭𝐚𝐧−𝟏
𝒚
]√𝟏 + 𝒙𝟐 dx
√𝟏+𝒙𝟐 √𝟏+𝒙𝟐 𝟎
𝟏𝝅 𝟏
∴ I = ∫𝟎 dx
𝟒 √𝟏+𝒙𝟐
𝝅 𝟏
∴I= [𝒍𝒐𝒈 (𝒙 + √𝟏 + 𝒙𝟐 ) ]
𝟒 𝟎
𝝅
∴I= 𝒍𝒐𝒈(𝟏 + √𝟐)
𝟒
𝒅𝒚
Q.2. (a) Solve xy(1+x𝒚𝟐 ) =𝟏 [6]
𝒅𝒙
𝒅𝒙
Ans: ∴ = 𝒙𝒚 + 𝒙𝟐 𝒚𝟑
𝒅𝒚
𝟏 𝒅𝒙 𝟏 𝟏
∴ - 𝒚 = 𝒚𝟑 Now, put − = 𝒗
𝒙𝟐 𝒅𝒚 𝒙 𝒙
𝒅𝒗 𝟏 𝒅𝒙 𝒅𝒗
∴ + 𝒗𝒚 = 𝒚𝟑 ……………………( = )
𝒅𝒚 𝒙𝟐 𝒅𝒚 𝒅𝒚
𝒚𝟐 𝒚𝟐
𝟏
- 𝒆 = 𝒆 (𝒚𝟐 − 𝟐) + c
𝟐 𝟐
𝒙
4
r=asin𝜃 y a
2a 2a x
r=a(1+cos𝜃)
𝝅 𝒂𝟐
= ∫𝝅 (𝒔𝒊𝒏𝟐 𝜽 − 𝟏 − 𝟐𝒄𝒐𝒔 𝜽 − 𝒄𝒐𝒔𝟐 𝜽) d𝜽
𝟐 𝟐
𝝅 𝒂𝟐
= ∫𝝅 (−𝟏 − 𝟐𝒄𝒐𝒔 𝜽 − 𝒄𝒐𝒔 𝟐𝜽) d𝜽
𝟐 𝟐
𝒂𝟐 𝒔𝒊𝒏𝟐𝜽 𝝅
= [ -𝜽 − 𝟐𝒔𝒊𝒏𝜽 − ] 𝝅
𝟐 𝟐 𝟐
𝒂𝟐 𝝅
I = [ (-𝝅 − 𝟎 − 𝟎) - (- − 𝟐 − 𝟎) ]
𝟐 𝟐
𝒂𝟐 𝝅
Required area is = I = (2 - )
𝟐 𝟐
f(x,y)= x + y
𝒌𝟏 = h.f(𝒙𝟎, 𝒚𝟎 ) = 0.2 f(0,1) = 0.2
𝒉 𝒌𝟏
𝒌𝟐 = h.f(𝒙𝟎 + , 𝒚𝟎 + ) = 0.2 f(0.1,1.1) = 0.24
𝟐 𝟐
5
𝒉 𝒌𝟐
𝒌𝟑 = h.f(𝒙𝟎 + ,𝒚𝟎 + ) = 𝟎. 𝟐𝒇(𝟎. 𝟏, 𝟏. 𝟏𝟐) = 0.244
𝟐 𝟐
Q.3 (a) Show that the length of curve 9a𝒚𝟐 =𝒙(𝒙 − 𝟑𝒂)𝟐 𝒊𝒔 𝟒√𝟑a. [6]
Ans : Curve : 9a𝒚𝟐 =𝒙(𝒙 − 𝟑𝒂)𝟐 ………… (1)
The given curve is strophoid.
(0,0) (3a,0) x
𝒅𝒚 (𝒙−𝟑𝒂)𝟐 (𝒙−𝒂)𝟐
∴ ( )𝟐 = ……………… from (1)
𝒅𝒙 𝟒𝒂 𝒙 (𝒙−𝟑𝒂)𝟐
𝒅𝒚 (𝒙−𝒂)𝟐
∴ ( )𝟐 =
𝒅𝒙 𝟒𝒂𝒙
6
𝟑𝒂 𝒅𝒚 𝟑𝒂 (𝒙−𝒂)𝟐 𝟑𝒂 (𝒙+𝒂)𝟐
S =∫𝟎 √𝟏 + ( )𝟐 𝒅𝒙 = ∫𝟎 √𝟏 + 𝒅𝒙 = ∫𝟎 √ 𝒅𝒙
𝒅𝒙 𝟒𝒂𝒙 𝟒𝒂𝒙
𝟑𝒂 𝒙+𝒂
∴ S = ∫𝟎 𝒅𝒙
𝟐 √ 𝒙√ 𝒂
𝟏 𝟑𝒂 𝒙+𝒂
∴S= ∫ 𝒅𝒙
𝟐√ 𝒂 𝟎 √𝒙
𝟏 𝟐 𝒙 √𝒙 𝟑𝒂
= [ + 2√𝒙 ]
𝟐√𝒂 𝟑 𝟎
𝟏 𝟐 𝒂√𝟑𝒂
= ( + 2√𝟑𝒂 )
𝟐√𝒂 𝟏
𝟏 𝟏+√𝟏−𝒚𝟐
(b) Change the order of integration of ∫𝟎 ∫−√𝟐𝒚−𝒚𝟐 𝒇(𝒙, 𝒚)𝒅𝒙𝒅𝒚. [6]
𝟏 𝟏+√𝟏−𝒚𝟐
Ans : Let I = ∫𝟎 ∫−√𝟐𝒚−𝒚𝟐 𝒇(𝒙, 𝒚)𝒅𝒙𝒅𝒚
𝒙𝟐 + (𝒚 − 𝟏)𝟐 = 𝟏
y=1
R1 R2
(𝒙 − 𝟏)𝟐 + 𝒚𝟐 = 𝟏
7
Divide the region R into R1 and R2
∴ R = R1 ∪ R2
After changing the order of integration ,
For region R1 : 𝟎 ≤ 𝒚 ≤ 𝟏 − √𝟏 − 𝒙𝟐
𝟎≤𝒙≤𝟏
(c) Find the volume of the paraboloid 𝑥 2 + 𝑦 2 = 4z cut off by the plane 𝒛 = 𝟒
[8]
Ans: Paraboloid : 𝒙𝟐 + 𝒚𝟐 = 𝟒𝒛 Plane : 𝒛 = 𝟒
z
𝒛=𝟒
𝒙𝟐 + 𝒚𝟐 = 𝟒𝒛
y
𝟎≤𝒓≤𝟒
𝝅
0≤𝜽≤
𝟐
𝝅
𝟒 𝒓𝟒
𝟒
=𝟒 ∫𝟎 ∫𝟎 [
𝟐 𝟒𝒓 − ] 𝒓𝟐 𝒅𝒓 𝒅𝜽
𝟏𝟔
𝟒
𝝅
𝟒 𝒓𝟑
= 𝟒 ∫𝟎 ∫𝟎 ( 𝟒𝒓 −
𝟐 ) 𝒅𝒓 𝒅𝜽
𝟒
𝝅
𝒓𝟒 𝟒
= 𝟒 ∫𝟎 [ 𝟐 𝒓𝟐 −
𝟐 ] 𝐝𝛉
𝟏𝟔 𝟎
𝝅
= 𝟒 ∫𝟎 (𝟑𝟐 − 𝟏𝟔) 𝐝𝛉
𝟐
𝑽 = 𝟑𝟐 𝝅 cubic units
𝟏 𝒙𝒂 −𝟏
Q.4 (a) Show that ∫𝟎 dx = log (a+1) [6]
𝐥𝐨𝐠 𝒙
𝟏 𝒙𝒂 −𝟏
Ans : let I = ∫𝟎 dx
𝐥𝐨𝐠 𝒙
differentiate w.r.t a ,
𝒅𝑰(𝒂) 𝒅 𝟏 𝒙𝒂 −𝟏
= ∫ dx
𝒅𝒂 𝒅𝒂 𝟎 𝐥𝐨𝐠 𝒙
𝒅𝑰(𝒂) 𝟏 𝝏 𝒙𝒂 −𝟏
∴ = ∫𝟎 𝒅𝒙 ………{ D.U.I.S f(x)}
𝒅𝒂 𝝏𝒂 𝐥𝐨𝐠 𝒙
9
𝒅𝑰(𝒂) 𝟏 𝒙𝒂 .𝐥𝐨𝐠 𝒙 𝒅𝒙𝒂
∴ = ∫𝟎 dx ………{ = 𝒙𝒂 . 𝐥𝐨𝐠 𝒂 }
𝒅𝒂 𝐥𝐨𝐠 𝒙 𝒅𝒂
𝒅𝑰(𝒂) 𝟏
∴ = ∫𝟎 𝒙𝒂 𝒅𝒙
𝒅𝒂
𝒅𝑰(𝒂) 𝒙𝒂+𝟏 𝟏
∴ =[ ]
𝒅𝒂 𝒂+𝟏 𝟎
𝒅𝑰(𝒂) 𝟏
∴ = −𝟎
𝒅𝒂 𝒂+𝟏
𝒅𝑰(𝒂) 𝟏
∴ =
𝒅𝒂 𝒂+𝟏
And
From eqn (2), I(0)= c
∴c=0
∴ I = log(a+1) Hence proved.
𝒅𝒚
(b) If 𝒚 satisfies the equation = 𝒙𝟐 𝒚 − 𝟏 𝒘𝒊𝒕𝒉 𝒙𝟎 = 𝟎, 𝒚𝟎 = 𝟏 using
𝒅𝒙
Taylor’s Series Method find 𝒚 𝒂𝒕 𝒙 = 𝟎. 𝟏 (take h=0.1). [6]
𝒅𝒚
Ans : = 𝒙𝟐 𝒚 − 𝟏 𝒙𝟎 = 𝟎, 𝒚𝟎 = 𝟏 , 𝒉 = 𝟎. 𝟏
𝒅𝒙
To find : 𝒚(𝟎. 𝟏)
𝒚 ′ = 𝒙𝟐 𝒚 − 𝟏 , 𝒚′𝟎 = −𝟏
𝒚′′ = 𝒙𝟐 𝒚′ + 𝟐𝒙𝒚 , 𝒚′′
𝟎 = 𝟎
Taylor’s series is :
10
𝒉𝟐 𝒉𝟑
𝒚 = 𝒚𝟎 + 𝒉. 𝒚′𝟎 + 𝒚′′
𝟎 + 𝒚′′′
𝟎 +⋯
𝟐! 𝟑!
(𝟎.𝟏)𝟑
∴ 𝒚(𝟎. 𝟏) = 𝟏 + 𝟎. 𝟏(−𝟏) + 𝟎 + (𝟐)
𝟑!
∴ 𝒚(𝟎. 𝟏) = 𝟎. 𝟗𝟎𝟎𝟑
𝟏 𝒙𝟐
(c) Find the value of the integral ∫𝟎 𝒅𝒙 using (i)Trapezoidal rule (ii)
𝟏+𝒙𝟑
a=0 , b=1
𝒃−𝒂 𝟏
Dividing limits into 4 parts i.e n=4 ∴h= = = 𝟎. 𝟐𝟓
𝒏 𝟒
𝒉
(i) Trapezoidal rule : I = [ 𝑿 + 𝟐𝑹] -----------------(1)
𝟐
∴ I = 0.2323
(ii) Simpson’s (𝟏/𝟑)𝒓𝒅 rule :
𝒉
I = [ 𝑿 + 𝟐𝑬 + 𝟒𝑶 ] ---------------(2)
𝟑
∴ I = 0.23108
11
(iii) Simpson’s (𝟑/𝟖)𝒕𝒉 rule :
𝟑𝒉
I= [ 𝑿 + 𝟐𝑻 + 𝟑𝑹 ] -------------(3)
𝟖
∴ I = 0.2008
𝝏𝑴 𝝏𝑵
≠
𝝏𝒚 𝝏𝒙
𝟏 𝒚 𝟏 𝒙𝒚
∫ 𝑴𝟏 𝒅𝒙 = ∫ (𝟐𝒙 − 𝟐) 𝒅𝒙 = (𝒍𝒐𝒈 𝒙) −
𝟐 𝟐
𝝏 −𝒙
𝝏𝒚
∫ 𝑴𝟏 𝒅𝒙 = 𝟐
𝝏 −𝟏 −𝟏
∫[ 𝑵𝟏 − 𝝏𝒚 ∫ 𝑴𝟏 𝒅𝒙 ]𝒅𝒚 = ∫ 𝟐𝒚 𝒅𝒚 = 𝟐
(𝒍𝒐𝒈 𝒚)
√𝒙 𝒙𝒚
∴ 𝒍𝒐𝒈 ( )− =𝒄
√𝒚 𝟐
𝒙𝟐 𝒚𝟐 𝒛𝟐 𝒙𝟐 𝒚𝟐
(b) Evaluate ∫ ∫ ∫ √𝟏 − 𝟐 − 𝟐 − 𝒅𝒙 𝒅𝒚 𝒅𝒛 over the ellipsoid 𝟐 + +
𝒂 𝒃 𝒄𝟐 𝒂 𝒃𝟐
𝒛𝟐
= 𝟏. [8]
𝒄𝟐
𝒙𝟐 𝒚𝟐 𝒛𝟐
Ans : Ellipsoid : 𝟐
+ 𝟐
+
𝒂 𝒃 𝒄𝟐
z
𝒙𝟐 𝒚𝟐 𝒛𝟐
𝒂𝟐
+ 𝒃 𝟐 + 𝒄𝟐 = 𝟏
𝒙𝟐 𝒚𝟐 𝒛𝟐
𝒇(𝒙, 𝒚, 𝒛) = √𝟏 − 𝟐
− 𝟐
− = √𝟏 − 𝒓𝟐 = 𝒇(𝒓, 𝜽, ∅)
𝒂 𝒃 𝒄𝟐
Limits : 𝟎≤𝒓≤𝟏
𝝅
𝟎≤𝜽≤
𝟐
𝝅
𝟎≤∅≤
𝟐
13
∴ I = 𝟖 ∫ ∫ ∫ √𝟏 − 𝒓𝟐 𝒂𝒃𝒄 𝒓𝟐 𝒔𝒊𝒏 𝜽 𝒅𝒓 𝒅𝜽 𝒅∅
𝝅 𝝅
𝒓
= 𝟖 ∫𝟎 ∫𝟎 ∫𝟎 √𝟏 − 𝒓𝟐 𝒂𝒃𝒄 𝒓𝟐 𝒔𝒊𝒏 𝜽 𝒅𝒓 𝒅𝜽 𝒅∅
𝟐 𝟐
𝝅 𝝅
𝒓
= 𝟖 𝒂𝒃𝒄 ∫𝟎𝟐 𝒔𝒊𝒏 𝜽 𝒅𝜽 ∫𝟎𝟐 𝒅∅ ∫𝟎 √𝟏 − 𝒓𝟐 𝒓𝟐 𝒅𝒓
𝝅 𝝅 𝝅
= 𝟖 𝒂𝒃𝒄 [−𝒄𝒐𝒔 𝜽] 𝟐 [ ∅ ] 𝟐 ∫𝟎 𝒄𝒐𝒔 𝒕. 𝒔𝒊𝒏𝟐 𝒕. 𝒄𝒐𝒔 𝒕 𝒅𝒕 ---------{ put r = sint}
𝟐
𝟎 𝟎
𝝅 𝝅
= 𝟖 𝒂𝒃𝒄 ( ) ( ) …………{ usi𝜷 𝒇𝒏 }
𝟐 𝟖
𝝅𝟐
∴I = (𝒂𝒃𝒄)
𝟒
𝒅𝟐 𝒚 𝒅𝒚
(c) Evaluate (𝟐𝒙 + 𝟏)𝟐 − 𝟐(𝟐𝒙 + 𝟏) − 𝟏𝟐𝒚 = 𝟔𝒙 [8]
𝒅𝒙𝟐 𝒅𝒙
𝒅𝟐 𝒚 𝒅𝒚
Ans : (𝟐𝒙 + 𝟏)𝟐 𝟐
− 𝟐(𝟐𝒙 + 𝟏) − 𝟏𝟐𝒚 = 𝟔𝒙 …………(1)
𝒅𝒙 𝒅𝒙
𝒆𝒛 −𝟏
Put (𝟐𝒙 + 𝟏) = 𝒆𝒛 => 𝒙=
𝟐
𝒅𝒛 𝟐 𝒅𝒚 𝒅𝒚 𝒅𝒛 𝒅𝒚 𝟐 𝒅
= but = = 𝟐 = Dy where D=
𝒅𝒙 (𝟐𝒙+𝟏) 𝒅𝒙 𝒅𝒛 𝒅𝒙 𝒅𝒛 (𝟐𝒙+𝟏) 𝒅𝒛
𝒅𝒚
∴ (2x+1) = 𝟐 𝑫𝒚
𝒅𝒙
𝒅𝟐 𝒚
∴ (𝟐𝒙 + 𝟏)𝟐 = 𝟐𝟐 𝑫 (𝑫 − 𝟏)𝒚
𝒅𝒙𝟐
From (1),
𝒆𝒛 −𝟏
𝟒𝑫(𝑫 − 𝟏)𝒚 − 𝟒 𝑫𝒚 − 𝟏𝟐𝒚 = 𝟔( )
𝟐
(𝟒 𝑫𝟐 − 𝟖𝑫 − 𝟏𝟐)𝒚 = 𝟑(𝒆𝒛 − 𝟏)
For complementary solution ,
(𝟒 𝑫𝟐 − 𝟖𝑫 − 𝟏𝟐) = 𝟎
∴ 𝑫 = −𝟏, 𝟑
∴ 𝒚𝒄 = 𝒄𝟏 𝒆−𝒛 + 𝒄𝟐 𝒆𝟑𝒛
For particular integral ,
𝟏
𝒚𝒑 = 𝑿
𝒇(𝑫)
14
𝟏
𝒚𝒑 = (𝟑(𝒆𝒛 − 𝟏))
𝟒𝑫𝟐 −𝟖𝑫−𝟏𝟐
𝟑 𝟏
∴ 𝒚𝒑 = (𝒆𝒛 − 𝟏) put D = a = 1 and D = a = 0
𝟒 𝑫𝟐 −𝟐𝑫−𝟑
𝟑 𝟏 𝒆𝒛
∴ 𝒚𝒑 = ( − )
𝟒 𝟑 𝟒
Resubstituting 𝒛 ,
𝟑 𝟏 (𝟐𝒙+𝟏)
∴ 𝒚𝒈 = 𝒄𝟏 (𝟐𝒙 + 𝟏)−𝟏 + 𝒄𝟐 (𝟐𝒙 + 𝟏)𝟑 + ( − )
𝟒 𝟑 𝟒
Q.6.(a) A resistance of 100 ohms and inductance of 0.5 henries are connected
in series With a battery of 20 volts. Find the current at any instant if
𝒅𝒊
the relation between L,R,E is L + 𝑹𝒊 = 𝑬. [6]
𝒅𝒕
𝒅𝒊
Ans : L + 𝑹𝒊 = 𝑬
𝒅𝒕
𝒅𝒊 𝑹𝒊 𝑬
∴ + =
𝒅𝒕 𝑳 𝑳
Solution is given by ,
𝑹 𝑹
)𝒅𝒕 )𝒅𝒕 𝑬
𝒊. 𝒆∫( 𝑳 = ∫ 𝒆∫( 𝑳 . 𝒅𝒕 + 𝒄
𝑳
𝑬 𝒆(𝑹𝒕/𝑳)
∴ 𝒊. 𝒆(𝑹𝒕/𝑳) = +𝒄
𝑹
𝑬
At t=0, i=0 ∴c=-
𝑹
𝑬 𝒆(𝑹𝒕/𝑳) −𝑬
∴ 𝒊. 𝒆(𝑹𝒕/𝑳) = +
𝑳 𝑹
𝑬
∴𝒊 = (𝟏 − 𝒆−(𝑹𝒕/𝑳) )
𝑹
15
𝒅𝟐 𝒚 𝒅𝒚 𝒙
(b) Solve by variation of parameter method 𝟐 +𝟑 + 𝟐𝒚 = 𝒆𝒆 .
𝒅𝒙 𝒅𝒙
[6]
𝒅𝟐 𝒚 𝒅𝒚 𝒙
Ans : +𝟑 + 𝟐𝒚 = 𝒆𝒆
𝒅𝒙𝟐 𝒅𝒙
𝒅
Put D = ∴ 𝑫𝟐 𝒚 + 𝟑𝑫𝒚 + 𝟐𝒚 = 𝟎
𝒅𝒙
y x=1 x=4
xy=4
𝒙
∴ 𝟎≤𝒚≤
𝟒
𝟏≤𝒙≤𝟒
𝒙
𝟒
∴I= ∫𝟏 ∫𝟎𝟒( 𝒙𝟐 𝒚 − 𝒙𝒚)𝒅𝒚 𝒅𝒙
𝑥
𝟒 𝒚𝟐 𝒚𝟐 𝒙
= ∫𝟏 [ 𝒙𝟐 − ] 4 𝐝𝐱
𝟐 𝟐 0
𝟒 𝟖
= ∫𝟏 (𝟖 − ) 𝒅𝒙
𝒙
𝟒
= [ 𝟖𝒙 − 𝟖𝒍𝒐𝒈 𝒙 ] 𝟏
∴ I = 𝟖(𝟑 − 𝟐 𝒍𝒐𝒈 𝟐)
17